“Троїста музика” як різновид автентичного та самодіяльного народноінструментального виконавства Західної України 1940–1980-х років - Дрозда, П. (Студії мистецтвознавчі, 2008)
During the last third of the past century a considerable place in the scientific and popular scientific literatures was occupied with the labours devoted to the development of the different kinds of amateur performances, specifically to the instrumental execution. These works that were aimed at popularization of the mass art conception as the organized variety of artistic activity of the broad masses within the framework of unique united Soviet socio-cultural space however enable to a great extent to learn the peculiarities of adaptive processes within the limits of musical, in particular folk-lore, cultures in the separate loci and regions with their originality and distinction. Therefore elucidation of one of the most popular varieties of the Ukrainian ensemble execution, particularly on Western Ukraine, is the purpose of the proposed investigation.